Graduate students' attitudes & self-directed for lifelong learning in foreign language environment - Sari, Desy Mutia; Ashadi, Ashadi (LingTera, 2020)
The student's attitude is needed to be self-directed learners to maintain lifelong learning in the ever-changing world. Thus, this study aimed to reveal whether graduate students' self-directed skills and attitudes vary based on university type and gender. Also, this study explored the relationship between graduate students' attitudes and self-directed lifelong learning skills then, further identified the lowest attitudes predictors for SDL, and analyzed how the students perceive the lecturer's role in self-directed learning. In a mixed-method study, 92 students from two selected public universities took questionnaires to measure their attitudes and self-directed learning and four students involved in the semi-structured interview. The obtained results showed that SDL and attitudes were found not to vary based on the university type. However, gender made a significant difference in SDL in favour of female students. Then, attitudes variable statistically significantly predicted students' SDL and perceptions of confidence and ability that emerged as the attitude dimension, seemed to be the lowest associated with the students' SDL. The majority of the students are still unaware of the SDL behaviour and see the lecturer as a factor that decisively affects them in developing greater independence. Further theoretical and practical implications are discussed.